I remember answering the same question, but you didn't attach any photos. But I remember that the answer is the first one.
I hope I helped. Stay safe and God bless!
- Eli <3
Answer:
(-1/3; 4)
Step-by-step explanation:
(-2, -1) , (-1, 6 ) and (2, 7).
x=(-2-1+2)/3= -1/3
y=(-1+6+7)/3=12/3=4
=> (-1/3; 4)
Answer:
the answer 61 cups of chocolate
Step-by-step explanation:
briniest please
Hi again............. I am glad to help you again.
6x + 35 + 9x = 15x(x+4) -25
6x + 35 + 9x = 15x² + 60x - 25
15x + 35 = 15x² + 60x - 25
Now, we gonna put all the common terms together
15x - 60x + 35 + 25 - 15x² =
-45x + 60 - 15x² = 0
Now, we need to factorize
-15(x-1)(x+4)=0
Set factors equal to 0
x -1 = 0 or x + 4 = 0
x = 1 or x = 4
I hope that's help !